Strategi Humas Pemerintah Provinsi Sumatera Selatan Dalam Membangun Citra Positif Pemerintah Daerah - Suhaini Oktari; Aliasan Aliasan; Muslimin Muslimin (Program Studi Jurnalistik, Universitas Islam Negeri Raden Fatah Palembang, 2023)
Public Relations Strategy for the Government of South Sumatra Province in Building a Positive Image of Local Government. The research was conducted to find out how the strategies used by public relations in building a positive image. In this case the main focus is the public relations of the provincial government. As we know that government public relations is under the auspices of the government agency of South Sumatra Province. In general, the task of public relations is to build a positive image of an organization. The Public Relations of the Government of South Sumatra Province itself has a task that has been regulated in South Sumatra Governor Regulation Number 55 of 2016, which is to provide administrative services in carrying out the duties and functions of regional apparatus in the field of public relations and protocol. This study uses a qualitative descriptive research method. In addition, this research is a field research, therefore all the necessary data will be obtained from primary data, namely obtaining data from informants who come directly from the Public Relations of the South Sumatra Provincial Government and secondary data in the form of writing, pictures or other media related to the Public Relations of the South Sumatra Provincial Government. . After that, when the data has been collected, then the data is analyzed using a qualitative descriptive method. Until in the end, this research found the common thread of the problem. The results of the study show that the strategy used by the Public Relations of the South Sumatra Provincial Government is to follow technological advances by utilizing all available media and collaborating with all media and related agencies.